2003
DOI: 10.1097/01.ju.0000055781.07630.aa
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Controlled Quantitative Study of Ultrastructural Changes in the Underactive Detrusor

Abstract: There were distinct morphological changes in the detrusor associated with bladder dysfunction with approximately 4 times more disruptive cells in patients with an underactive bladder. However, there was no correlation between age and number of disruptive cells, suggesting that this is not a process of aging per se. Ultrastructure studies may have a role as an adjunct to urodynamics in the diagnosis of bladder dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 7 publications
2
43
1
3
Order By: Relevance
“…If there is less/absent efferent stimulation of the detrusor, then there will be an underactive (or absent) detrusor contraction. Lack of efferent stimulation could represent a potential cause of aberrant detrusor muscle cell de-differentiation as seen in studies by Elbadawi et al [18] and Brierly et al [19], and thus indirectly contribute to impaired detrusor function.…”
Section: Roles Of Detrusor Motor Function Central Processing Efferementioning
confidence: 95%
See 1 more Smart Citation
“…If there is less/absent efferent stimulation of the detrusor, then there will be an underactive (or absent) detrusor contraction. Lack of efferent stimulation could represent a potential cause of aberrant detrusor muscle cell de-differentiation as seen in studies by Elbadawi et al [18] and Brierly et al [19], and thus indirectly contribute to impaired detrusor function.…”
Section: Roles Of Detrusor Motor Function Central Processing Efferementioning
confidence: 95%
“…The decline of detrusor performance in DU is greater than in normative aging. Bladders with impaired contractility, as studied by Brierly et al [19], were found to have four times more disruptive cells (eg, sarcoplasmic vacuolation, sequestration or blebbing, cell shriveling, cell fragmentation, presence of cell debris in the intercellular spaces) than in age-matched controls. Because this fi nding did not correlate with age or sex, it raises the question of whether muscle disruption correlated with DU may represent a distinct disease entity rather than a normal aging process.…”
Section: Roles Of Detrusor Motor Function Central Processing Efferementioning
confidence: 97%
“…If this process were more severe, significant muscle and axonal degeneration (as seen in patients with DU 16,17 ) might amplify the effect of passive biomechanical changes, as well as directly impair afferent and efferent neurotransmission, thus contributing to clinical DU rather than more mild and perhaps subclinical voiding dysfunction. If similar changes occur in the urethra, diminished urethral-detrusor feedback could contribute to inefficient voiding.…”
Section: -61mentioning
confidence: 96%
“…Decreased detrusor contractility in UAB can result from a lack of contractile stimulus (acetylcholine and ATP) [77] and/or a lack of tissue responsiveness due to irreversible changes in the bladder wall described as sarcopenia (loss of muscle tissue, increased collagen deposition) [26,78]. Several factors may contribute to altered excitationcontraction coupling mechanisms including changes in the properties and density of calcium [79] and potassium channels, gap junctions and receptors in detrusor smooth muscles of aged and UAB patients.…”
Section: Models Of Myogenic Uabmentioning
confidence: 99%